Strategi Pengembangan Manajemen Sumber Daya Manusia Era Society 5.0 di Madrasah - Fahmi Khumaini; Nurul Mahruzah Yulia; Moh. Yusuf Efendi (Al-fahim : Jurnal Manajemen Pendidikan Islam, 2023)
This study seeks to reveal an initiative on the strategy of developing the quality of Islamic educational institutions at the madrasah level through the development of Human Resource Management. This research uses the literature study method, where literature searches in the form of relevant theories, including literature on human resource management in Islamic educational institutions, especially related to madrasah. Literature studies interpret data in descriptive analysis. References or literature are obtained from research results published in national or international journals, articles, books, and websites relevant to the discussion. This study seeks to answer problems about 1) The position of madrasah in the education system in Indonesia; 2) Human Resource Management in improving the quality of education in Madrasah which includes basic concepts and strategies. The results of this study show that, the strategy of developing Human Resource management in Madrasah is a cultural concept that is coherent with the vision and mission of the institution, and is aware that the culture of human resource development management as a cognitive representation is formed by the overall structure in madrasah educational institutions. A good organizational culture is characterized by norms and values that support excellence, teamwork, profitability, honesty, service orientation, integrity, and commitment to the madrasah educational organization/institution. So that madrasah has the ability to develop innovative and adaptive human resources to answer the challenges of Society 5.0.